Elementary Energy Transfer Pathways in Allochromatium vinosum Photosynthetic Membranes - Lüer, Larry (Biophys J, 2015)
Allochromatium vinosum (formerly Chromatium vinosum) purple bacteria are known to adapt their light-harvesting strategy during growth according to environmental factors such as temperature and average light intensity. Under low light illumination or low ambient temperature conditions, most of the LH2 complexes in the photosynthetic membranes form a B820 exciton with reduced spectral overlap with LH1. To elucidate the reason for this light and temperature adaptation of the LH2 electronic structure, we performed broadband femtosecond transient absorption spectroscopy as a function of excitation wavelength in A. vinosum membranes. A target analysis of the acquired data yielded individual rate constants for all relevant elementary energy transfer (ET) processes. We found that the ET dynamics in high-light-grown membranes was well described by a homogeneous model, with forward and backward rate constants independent of the pump wavelength. Thus, the overall B800→B850→B890→ Reaction Center ET cascade is well described by simple triexponential kinetics. In the low-light-grown membranes, we found that the elementary backward transfer rate constant from B890 to B820 was strongly reduced compared with the corresponding constant from B890 to B850 in high-light-grown samples. The ET dynamics of low-light-grown membranes was strongly dependent on the pump wavelength, clearly showing that the excitation memory is not lost throughout the exciton lifetime. The observed pump energy dependence of the forward and backward ET rate constants suggests exciton diffusion via B850→ B850 transfer steps, making the overall ET dynamics nonexponential. Our results show that disorder plays a crucial role in our understanding of low-light adaptation in A. vinosum.